2011
DOI: 10.1155/2011/868546
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Behavior ofPraon volucre(Hymenoptera: Braconidae) a Parasitoid ofSitobion avenae(Hemiptera: Aphididae) on Wheat

Abstract: Host stage preference, functional response and, mutual interference of Praon volucre (Haliday) (Hym.: Braconidae) parasitizing the grain aphid, Sitobion avenae (Fabricius) (Hem.: Aphididae), were investigated under laboratory conditions. Host stage preference was evaluated at 25 ± 1• C, 60 ± 5% relative humidity and a photoperiod of 16:8 h (L : D), under choice and no-choice tests. Functional response was done under five constant temperatures (10, 15, 20, 25, and 30 • C), 60 ± 5% relative humidity and a phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In this experiment, A. matricariae parasitized all stages of M. persicae nicotianae , which it more preferred third- and fourth-instar nymphs to oviposition. To date, a large number of studies have been conducted on the host stage preference of aphid parasitoids (Rakhshani et al ., 2004; Talebi et al ., 2006; Farhad et al ., 2011; Stacconi et al ., 2015; Yang et al ., 2015). Our findings are also in agreement with the authors (Rakhshani et al ., 2004; Talebi et al ., 2006; Tazerouni et al ., 2011) who reported the third- and fourth-instar nymphs of host aphids were the preferred host stages by the aphid parasitoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this experiment, A. matricariae parasitized all stages of M. persicae nicotianae , which it more preferred third- and fourth-instar nymphs to oviposition. To date, a large number of studies have been conducted on the host stage preference of aphid parasitoids (Rakhshani et al ., 2004; Talebi et al ., 2006; Farhad et al ., 2011; Stacconi et al ., 2015; Yang et al ., 2015). Our findings are also in agreement with the authors (Rakhshani et al ., 2004; Talebi et al ., 2006; Tazerouni et al ., 2011) who reported the third- and fourth-instar nymphs of host aphids were the preferred host stages by the aphid parasitoids.…”
Section: Discussionmentioning
confidence: 99%
“…Type II functional response is more frequent in different parasitoids (Fathipour et al ., 2006; Poncio et al ., 2016) and has also been reported for A. matricariae on different host aphid species such as Aphis fabae Scopoli (Hemiptera: Aphididae) (Tahriri et al ., 2007) and Aphis gossypii Glover (Hemiptera: Aphididae) (Zamani et al ., 2006). Also, type II functional response has been often determined in other aphid parasitoids such as P. volucre on S. avenae (Farhad et al ., 2011), D. rapae on Diuraphis noxia (Mordvilko) (Hemiptera: Aphididae) (Tazerouni et al ., 2011), A. colemani on A. gossypii (Zamani et al ., 2006), P. volucre on M. persicae (Tazerouni et al ., 2016 b ), and L. fabarum on A. craccivora (Takalloozadeh et al ., 2005). By contrast, type III functional response which is density-dependent was reported for A. matricariae on M. persicae (Hart et al ., 1978; Tazerouni et al ., 2016 a , b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional response of Aenasius bambawalei Hayat (Hymenoptera: Encyrtidae) to different densities of Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) has been determined to be of type II (Feng et al 2014;Joodaki et al 2018). Also, type II functional response has been reported for other parasitoids, such as Praon volucre (Haliday) (Hymenoptera: Braconidae) attacking Sitobion avenae (Fabricius) (Hemiptera: Aphididae) (Farhad et al 2011) Parasitoid with a type II functional response exerts an inverse, density-dependent action on the pest, whereas a parasitoid with a type III functional response acts in a positive, density-dependent manner. Therefore, a parasitoid with a type III functional response could be a better regulator agent than one having a type II functional response, which can destabilize the pest-natural enemy interaction (Dunn and Hovel 2020).…”
Section: Effect Of Host Density On Parasitism Progeny and Sex Ratiomentioning
confidence: 91%
“…He and Wang (2014) demonstrated that parasitoid Platygaster demades Walker (Hymenoptera: Platygastridae) attacking Dasineura mali Kieffer (Diptera: Cecodomyiidae) displayed a type II functional response in the laboratory, but showed a type III in the field where females were able to freely search and disperse. The reports of type II functional response in A. lopezi and other parasitoid species (Farhad et al 2011;Hanan et al 2017) might be due to a restrictive experimental arena (van Lenteren and Bakker 1978). The form of functional response on its own does not determine the success or failure of parasitoids in biological control (Fernandez-Arhex and Corley 2003;Tazerouni et al 2019).…”
Section: Effect Of Host Density On Parasitism Progeny and Sex Ratiomentioning
confidence: 99%